Bacterial sexually transmitted-diseases – the threat of the 21st century - Książek, Piotr; Herda, Jolanta; Raszewska, Magdalena; Kawałek, Magdalena; Mojsym, Sylwia (Polish Journal of Public Health, 2011)
The bacterial STDs have been always a part of human life. Societies from all over the world tackle with this relevant health problem. Three hundred and forty million of new STD cases are revealed every year according to WHO. In most cases symptoms are barelynoticeable, however they cause chronic and infectious diseases that may lead to serious, long-lasting consequences. There are some patients who choose self-treatment before they visit specialists. The cause of that is the perception of STDs as embarrassing diseases. The aim of this article is to introduce the most frequent bacterial STDs, their risk factors, symptoms and complications. We analyzed with a particular attention available data and reports about current epidemiological situation in Poland. Results are unfavorable. It is presumed that most cases of sexually transmitted diseases are not diagnosed or registered properly. This is the reason why the particular attention should be drawn to certain fields of health promotion. Research has revealed low level of medical knowledge in most exposed societies. It seems that most important way to limit STD is to spread knowledge widely among patients and their doctors.